2009
DOI: 10.1007/s00376-009-8198-0
|View full text |Cite
|
Sign up to set email alerts
|

Variability of soil moisture and its relationship with surface albedo and soil thermal parameters over the Loess Plateau

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 135 publications
(97 citation statements)
references
References 17 publications
6
83
0
Order By: Relevance
“…These discrepancies could be caused by non-uniform daily changes in soil water content before and after rainfall events during the growing seasons. As a result of non-linear changes in the soil particles -water -air paths for heat conduction during wettingdrying processes, both thermal conductivity and heat capacity of soils with different porosity and bulk density usually showed: -a non-linear and more or less rapid increase with increasing soil water content, and -a non-linear decrease with declining soil water content (Guan et al, 2009;Smits et al, 2009;Usowicz, 1995). The results of the sensitivity analysis demonstrated that the soil temperatures predicted by the SWAP model, compared to those after the DNDC model, had a lower variability at the relative changes in daily air temperature ranking from ±4-5% to ±15-17% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These discrepancies could be caused by non-uniform daily changes in soil water content before and after rainfall events during the growing seasons. As a result of non-linear changes in the soil particles -water -air paths for heat conduction during wettingdrying processes, both thermal conductivity and heat capacity of soils with different porosity and bulk density usually showed: -a non-linear and more or less rapid increase with increasing soil water content, and -a non-linear decrease with declining soil water content (Guan et al, 2009;Smits et al, 2009;Usowicz, 1995). The results of the sensitivity analysis demonstrated that the soil temperatures predicted by the SWAP model, compared to those after the DNDC model, had a lower variability at the relative changes in daily air temperature ranking from ±4-5% to ±15-17% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The formula also referred empirical values from Ginoux et al (2012) and assume r eff = 1.2 µm, ρ = 2600 kg m −3 , Q ext = 2.5, and ε = 0.6 m 2 g −1 . This method not only modifies the maximum standard technique developed by Jordan et al (2010), its derived dust column burden also has a correlation coefficient of 0.73 with the ground-based lidar observation at the Semi-Arid Climate and Environment Observatory of Lanzhou University (SACOL) Guan et al, 2009;Liu et al, 2014), indicating its effectiveness in detecting anthropogenic dust. Figure 1 shows the global distribution of semi-arid regions along with the mean anthropogenic dust column burden from 2007 through 2010, demonstrating the wide spread of anthropogenic dust.…”
Section: Methods For Detecting Anthropogenic Dust Aerosolmentioning
confidence: 99%
“…In the northeastern ecotone between agriculture and animal husbandry, farmland has greater roughness and energy fluxes than the grassland in Tongyu (Feng et al, 2012) but less than the reed wetland in Panjin ). In the degraded grassland in western China, the oasis-desert transition zone is a cold source relative to the Gobi in Dunhuang (Wang et al, 2005;Zhang and Huang, 2004), and energy fluxes are different over different land surface due to vegetation, precipitation, and soil moisture in the Loess Plateau (Huang et al, 2008;Guan et al, 2009;Wang et al, 2010). Moreover, rapid urban expansion has changed heat fluxes in the Pearl River delta considerably (Lin et al, 2009) and has increased sensible heat flux in Beijing ).…”
Section: Introductionmentioning
confidence: 99%